Bank stress tests as an information device for emerging markets: The case of Russia - Zuzana Fungáčová; Petr Jakubik (Bank of Finland, Institute for Economies in Transition (BOFIT), 2012)
The recent financial crisis emphasised the need for effective financial stability analyses and tools for detecting systemic risk. This paper looks at assessment of banking sector resilience through stress testing. We argue such analyses are valuable even in emerging economies that suffer from limited data availability, short time series and structural breaks. We propose a top-down stress test methodology that employs relatively limited information to overcome this data problem. Moreover, as credit growth in emerging economies tends to be rather volatile, we rely on dynamic approach projecting key balance sheet items. Application of our proposed stress test framework to the Russian banking sector reveals a high sensitivity of the capital adequacy ratio to the economic cycle that shows up in both of the two-year macroeconomic scenarios considered: a baseline and an adverse one. Both scenarios indicate the need for capital increase in the Russian banking sector. Furthermore, given that Russia's banking sector is small and fragmented relative to advanced economies, the loss of external financing can cause profound economic stress, especially for medium-sized and small enterprises. The Russian state has a low public debt-to-GDP ratio and plays decisive role in the banking sector. These factors allow sufficient fiscal space for recapitalisation of problematic banks under both of our proposed baseline and adverse scenarios.
URN:NBN:fi:bof-201408071912
Keywords: G28; P34; G21; 330; stress testing; bank; Russia